Effect of reline material and denture base surface treatment on the impact strength of a denture base acrylic resin - da Cruz Perez, Luciano Elias; Machado, Ana Lucia [UNESP]; Canevarolo, Sebastiao Vicente; Vergani, Carlos Eduardo [UNESP]; Giampaolo, Eunice Teresinha; Pavarina, Ana Claudia [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
Objective:In this study, the effect of relining and surface treatment on the impact strength (IS) of a heat-polymerising denture base acrylic resin (Lucitone 550-L) was evaluated.Materials and methods:Rectangular bars of L were made (60 x 6 x 2 mm) and relined (2 mm) with the relining resins Ufi Gel Hard (UH) and Tokuso Rebase Fast (TR). Specimens relined with L and intact L, TR and UH specimens were also made (60 x 6 x 4 mm), for comparison. Before relining, the L surface was left untreated or wetted with methyl methacrylate monomer and/or the bonding agents (BA) supplied by manufacturers of the reline resins. V-notches were machined at the midpoint of the length of all specimens. The notches were made either across the width (Nw) or across the thickness of the specimens (Nth). The Charpy impact test was performed using a 0.5-J pendulum, which had been specially designed and constructed. Data were analysed separately for each notch position using one-way analysis of variance and Tukey honestly significant difference post-hoc test (p = 0.05).Results:The IS of L was similar to that of L/L. For the Nw notch, treating the denture base L with TR BA and relining with TR reline material produced the highest IS.Conclusion:The IS of specimens made from heat polymerising acrylic resin Lucitone 550 was increased after relining using the hard chairside reline resin TR with its proprietary BA.
Keywords: acrylic resins; relining; surface treatment; impact strength